The effects of climate change on rural-urban migration in the Moletjie community, Limpopo Province, South Africa - Trevor Rehaugetswe Modise (Indonesian Journal of Social and Environmental Issues (IJSEI), 2026)
Rural community members’ livelihoods are compromised by the fluctuating climatic hazards that result in severe conditions. This study aimed to explore the impact of climate change in rural communities, focusing on how rural-urban migration, as one of the indicators of climate change, affects the livelihood of community members. The study was qualitative; data were collected until saturation. In-depth interviews with an equal sample of 75 men and 75 women, making a total of 150 participants, gathered data on the effects of climate change in rural communities, focusing on how rural-urban migration as an element of climate change affects the livelihood of community members. Using content thematic analysis, the study analyzed the effects of climate change in local communities converging on how rural-urban migration affects community members’ well-being. The study reveals that climate change is negatively impacting community members’ way of living, as rural-urban migration is noted as a daunting issue in the community. The study further reveals that climate change results in rural-urban migration as community members are exposed to poverty, hunger, and malnutrition. The findings attest that ghost houses, family disconnection, and dislocation further predispose women and children to danger and hard labour. The study proposes the incorporation of traditional and government officials for employment opportunities and farming resources in rural areas. The study recommends government intervention by means of rural development. The study concludes that climate change is a great contributing factor to the livelihood of local communities, as community members are prone to hunger, unemployment, and poverty.